Expanding plastics recycling technologies: chemical aspects, technology status and challenges. Issue 23 (26th September 2022) - Li, Houqian; Aguirre-Villegas, Horacio A.; Allen, Robert D.; Bai, Xianglan; Benson, Craig H.; Beckham, Gregg T.; Bradshaw, Sabrina L.; Brown, Jessica L.; Brown, Robert C.; Cecon, Victor S.; Curley, Julia B.; Curtzwiler, Greg W.; et al.
Abstract : This paper reviewed the entire life cycle of plastics and options for the management of plastic waste to address barriers to industrial chemical recycling and further provide perceptions on possible opportunities with such materials. Abstract : Less than 10% of the plastics generated globally are recycled, while the rest are incinerated, accumulated in landfills, or leak into the environment. New technologies are emerging to chemically recycle waste plastics that are receiving tremendous interest from academia and industry. Chemists and chemical engineers need to understand the fundamentals of these technologies to design improved systems for chemical recycling and upcycling of waste plastics. In this paper, we review the entire life cycle of plastics and options for the management of plastic waste to address barriers to industrial chemical recycling and further provide perceptions on possible opportunities with such materials. Knowledge and insights to enhance plastic recycling beyond its current scale are provided. Outstanding research problems and where researchers in the field should focus their efforts in the future are also discussed.